2017
DOI: 10.1149/2.1071713jes
|View full text |Cite
|
Sign up to set email alerts
|

Enhancing Pt/C Catalysts for the Oxygen Reduction Reaction with Protic Ionic Liquids: The Effect of Anion Structure

Abstract: Protic ionic liquids (ILs) have been recently studied as a potential approach to enhance oxygen reduction reaction (ORR) activity of carbon supported platinum catalysts (Pt/C) for application in polymer electrolyte membrane fuel cells. The high oxygen solubility in the ILs was suggested as one of the main reasons for the accelerated reaction rates. Because the nature of the anion of the IL has been associated with increased oxygen solubility, in this work we survey a number of ionic liquids with various anions… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
143
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 63 publications
(152 citation statements)
references
References 63 publications
9
143
0
Order By: Relevance
“…Similarly, Huang et al reported that Pt/C modified with [MTBD][C 4 F 9 SO 3 ] ( Scheme S1 ) suffered 28% ECAS loss relative to the pristine Pt/C. 37 Nevertheless, our current work confirms that the effect of IL modification on ECAS depends sensitively on the specific structure of ILs, even for the ILs from the same category.…”
Section: Resultssupporting
confidence: 79%
See 2 more Smart Citations
“…Similarly, Huang et al reported that Pt/C modified with [MTBD][C 4 F 9 SO 3 ] ( Scheme S1 ) suffered 28% ECAS loss relative to the pristine Pt/C. 37 Nevertheless, our current work confirms that the effect of IL modification on ECAS depends sensitively on the specific structure of ILs, even for the ILs from the same category.…”
Section: Resultssupporting
confidence: 79%
“…This indicates that the presence of the IL phase can suppress the formation of oxygenated species on Pt, which is consistent with previous reports. 31 , 33 , 35 37 For the IL-modified Pt/C catalysts, the hydrophobicity of the IL phase at the Pt/C catalyst surfaces is thought to create a hydrophobic microenvironment at the interface between the catalyst and aqueous electrolyte, which can help preserve the active Pt sites from being partially oxidized or forming oxygenated species by repelling water molecules. 36 It should be be noted that the surface oxygenated species on Pt is considered to be nonreactive and will lead to blockage of Pt active sites.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Ionic liquids have emerged as a promising area in material science because of their tunable properties, allowing them to be used in a wide range of application such as: carbon dioxide capture, fuel cells, nanoparticle stabilization, and many more (Song et al, 2019;Huang et al, 2017;Wang et al, 2017). In this context, our group has been working on the synthesis of new cation moieties for ionic liquid designs.…”
Section: Structure Descriptionmentioning
confidence: 99%
“…30 By systematically changing the side chain length of the imidazolium cations, ([C n C 1 im][bis(trifluoromethylsulfonyl)imide(NTf 2 )], n = 2, 4, 6, and 10), a clear dependence of Pt catalytic activity on ORR for side chain length was observed, with the highest activity obtained using medium chain length IL (n = 4). 27 While the mechanism of the observed activity enhancement of IL remains elusive, the increased oxygen solubility, 24,31 inhibition of Pt oxidation, 27,30,32 and lower adsorption of nonreactive species 25,27,30 are considered among the factors that enhance ORR activity. A recent study by Zhang et al concluded that the presence of IL improved the electrochemical stability of Pt/C catalysts by suppressing the formation of oxygenated species and/or the initial oxidation of low-coordinating Pt sites at edges, corners, and/or defect Pt sites.…”
Section: Introductionmentioning
confidence: 99%